Review of the Fund's Income Position for FY 2017 and FY 2018. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
The Fund's total net income for FY 2017, including surcharges, is projected at about SDR 1.7 billion or some SDR 0.7 billion higher than expected in April 2016. This mainly reflects the IAS 19 adjustment (relating to reporting of employee benefits), which is expected to contribute about SDR 0.4 billion to net income, and higher investment income. Lending income is expected to be modestly lower than the April 2016 estimates. The paper recommends that GRA net income of SDR 1.2 billion for FY 2017 (which excludes projected income of the gold endowment), be placed equally to the special and general reserve. After the placement of GRA FY 2017 net income to reserves, precautionary balances are projected to reach SDR 16.4 billion at the end of FY 2017. The paper further proposes to transfer currencies equivalent to the increase in the Fund's reserves from the GRA to the Investment Account. In April 2016, the margin for the rate of charge was set at 100 basis points for the two years FY 2017 and FY 2018. The margin may be adjusted before the end of the first year of this two-year period (i.e., FY 2017) but only if warranted by fundamental changes in the underlying factors relevant for the establishment of the margin at the start of the two-year period. Staff does not propose a change in the margin. The projections for FY 2018 point to a net income position of SDR 0.7 billion. These projections are subject to considerable uncertainty and are sensitive to a number of assumptions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet